2017
DOI: 10.1123/ijspp.2016-0371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Critical Power and W′ Derived From 2 or 3 Maximal Tests

Abstract: The current study demonstrates that after 2 familiarization sessions, reliable CP and W' parameters can be obtained from trained cyclists using only 2 maximal-exercise trials. These results offer practitioners a practical, time-efficient solution for incorporating power-duration testing into applied athlete support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Fixed-duration maximal time trial efforts (TT): Details of these experimental procedures are provided elsewhere (Parker Simpson & Kordi, 2016). Briefly, all TT efforts began with participants increasing power output in the 10-to 15-s period prior to the start of a TT toward their pre-effort target power (see below for further information about 'TT target powers').…”
Section: Methodsmentioning
confidence: 99%
“…Fixed-duration maximal time trial efforts (TT): Details of these experimental procedures are provided elsewhere (Parker Simpson & Kordi, 2016). Briefly, all TT efforts began with participants increasing power output in the 10-to 15-s period prior to the start of a TT toward their pre-effort target power (see below for further information about 'TT target powers').…”
Section: Methodsmentioning
confidence: 99%
“…To address this issue, some authors have investigated whether a shorter recovery between trials affects CP and/or W'(15,45,63,85,97,105).Karsten et al (64) compared the conventional 24 h method with two experimental recovery durations of 3 h and 30 min. The authors observed that, in comparison with the standard 24-h-recovery protocol, the two shorter recovery protocols were sufficient to not affect CP (prediction error of 2.5% and 3.7% for the 3 h and 30 min recovery protocols, respectively, compared to 24 h).…”
mentioning
confidence: 99%
“…However, our sample size is similar to several other studies that investigated the critical power model in exercise. [8][9][10][11][23][24][25] From a practical point of view, the CHR seems to be an interesting alternative in exercise prescription to the load on the CP, since both indicators Table 3. Individual values of the HR at AT, RCP, and CHR measure and CHR estimated.…”
Section: Discussionmentioning
confidence: 99%